2021
DOI: 10.1302/2058-5241.6.200124
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity indices in orthopaedic surgery: a narrative review focused on hip and knee arthroplasty

Abstract: Comorbidity indices currently used to estimate negative postoperative outcomes in orthopaedic surgery were originally developed among non-orthopaedic patient populations. While current indices were initially intended to predict short-term mortality, they have since been used for other purposes as well. As the rate of hip and knee arthroplasty steadily rises, understanding the magnitude of the effect of comorbid disease on postoperative outcomes has become increasingly more important. Currently, the ASA classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Previous studies using objective health measures to predict medical complications and/or mortality have shown that decreased preoperative health status (measured using ASA grade, Charlson comorbidity, Elixhauser comorbidity measure, modi ed Frailty Index) was associated with negative shortterm postoperative outcomes after total joint arthroplasty [3,12,[24][25][26][27][28][29]. Presence of comorbidities has an impact on patient mortality and medical complications but also on hospital resources and reimbursement [10]. Inconsistence performance and sparse validation of theses indices to predict revision, reoperation, medical complications and mortality were observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies using objective health measures to predict medical complications and/or mortality have shown that decreased preoperative health status (measured using ASA grade, Charlson comorbidity, Elixhauser comorbidity measure, modi ed Frailty Index) was associated with negative shortterm postoperative outcomes after total joint arthroplasty [3,12,[24][25][26][27][28][29]. Presence of comorbidities has an impact on patient mortality and medical complications but also on hospital resources and reimbursement [10]. Inconsistence performance and sparse validation of theses indices to predict revision, reoperation, medical complications and mortality were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity is an important determinant of outcomes after surgical interventions. In the context of total hip arthroplasty (THA) this was con rmed regarding length of hospital stay, readmission after THA, revision surgery and postoperative mortality [1][2][3][4][5]. Comorbidity refers to one or more other diseases or medical conditions coexisting and not on the causal pathway of the disease of interest and evaluated by the clinician [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such uncontrolled comorbidities may have impacts on an individual's physiologic reserve [50], especially those who are undergoing an acute event (e.q. TKR surgery) [51]; (2) a history of internal cancer requiring surgery, neurological diseases, or falling fracture in legs before six months of surgery; (3) underwent simultaneously bilateral or a revision TKR; (4) patients who had a knee flexion ROM < 125 degrees at inpatient discharge; the details were described in the following (Section 2.6). A flowchart depicting the patient selection process and study group assignment is illustrated in Figure 1.…”
Section: Participantsmentioning
confidence: 99%